A case report: A rare case of infant gastrointestinal canthariasis caused by larvae of Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Anobiidae). Issue 1 (December 2016) - Sun, Xi; Wang, Li-Fu; Feng, Ying; Xie, Hui; Zheng, Xiao-Ying; He, Ai; Karim, Md; Lv, Zhi-Yue; Wu, Zhong-Dao
Abstract Background Canthariasis is a disease of humans caused by the infestation of beetle larvae. It is the second important insectal disease after myiasis. Several species of beetles are reported to cause the disease in gastrointestinal tract, urogenital system, nasal sinuses, ears and faces of mammals. The cigarette beetleLasioderma serricorne is a widespread and destructive pest that usually feeds on tobacco, tea, beans, cereal grains, and animal and plant specimen. While there was no previous evidence of human infestation by this worm, we report the first case ofL. serricorne infestation in a baby girl in China. Case presentation Here the case, an eight-month-old baby girl with irritable feeling, rubbing eyes, history of contact with mud and eating oranges twice during five days before attendance, and having "worms" in her stool was admitted to the First Affiliated Hospital of Sun Yat-sen University, Guangzhou, China. The clinical examination revealed that the pulse rate, blood pressure and temperature were regular, and the examination of the head, neck, and chest were unremarkable. The stool specimens containing "worms" were sent to the Department of Parasitology, Zhongshan School of Medicine, Sun Yat-sen University. The worms were recovered, studied morphologically using naked eyes and anatomical lens, PCR analyzed targeting cytochrome oxidase subunit 1 (COX1 ) and 18S rRNA genes, examined by sequence analyses of the PCR products and finally classified by phylogenetic analysis to identify their species. Based on the findings, the worms were diagnosed as the larvae ofL. serricorne . Conclusion This report implies that the baby had an infestation with the larvae ofL. serricorne in the gastrointestine. During contact with mud or eating oranges by the girl, worm eggs were swallowed into the stomach and resisted gastric acid digestion which eventually hatched into larvae and caused canthariasis. The 8 months girl had underdeveloped immune system which might facilitate the disease. This report implicates thatL. serricorne can infest human accidentally and cause canthariasis that may lead to severe damage to infant and older patient upon involvement of important organs of the body. The patients once diagnosed having canthariasis should be treated in time.